The life and works of F. Sionil Jose - Torres, Basilisa Concepcion O. (School of Library and Information Studies, University of the Philippines Diliman, 2007)
Most Filipino authors do not get the acclaim due to them because of the Colonial Mentality that exists in Philippine society. The Philippine educational system set up by the Americans during their occupation of the country has instilled a barrage of westernized thinkers in the populace that has remained throughout the years. F. Sionil Jose is one such author, though his writing has garnered awards and recognition internationally as well as locally, familiarity with his work is still limited. To be able to establish a wider audience and recognition of his writings, this bio-bibliography is being set forth to acknowledge and assist scholars in finding out about the man and his works.